Implementasi Model Pembelajaran POE (Predict, Observe, Explain) dengan Mengintegrasi Teknologi dalam Mengkonstruk Technological Literacy Mahasiswa Calon Guru IPA Sekolah Dasar - Deni Moh. Budiman (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2019)
This research was conducted to test the effectiveness of the application of the learning model of POE (Predict, Observe, Explain) by integrating technology in constructing technological literacy of elementary school science teacher candidates. The study was conducted by comparing learning using the POE model by integrating technology in the experimental class with without integrating technology in the control class. The research method used was a quasi-experimental research design with The Randomized Pretest - Posttest Control Group Design. The sample of this research is the students of elementary science teacher candidates selected by cluster random sampling. The research instrument used in the form of a test device to measure technological literacy with a reliability index of 0.94. The results showed that significantly learning using the POE model by integrating technology was more effective in increasing technological literacy compared to learning without integrating technology.